Surgical site infection after valvular or coronary artery bypass surgery: 2008–2011 French SSI national ISO-RAISIN surveillance. Issue 3 (November 2015) - Cossin, S.; Malavaud, S.; Jarno, P.; Giard, M.; L'Hériteau, F.; Simon, L.; Bieler, L.; Molinier, L.; Marcheix, B.; Venier, A.-G.; the ISO-RAISIN Steering Committee, †
Summary Background Multisite information regarding surgical site infection (SSI) rates for cardiac surgery programmes is not widely available. Ward characteristics that may affect outcomes have not been analysed previously. Aim To determine individual- and ward-level factors associated with SSI occurrence after coronary artery bypass grafting (CABG) and valvular surgery. Methods A dataset from the French national SSI database ISO-RAISIN 2008–2011 was used. Only adult patients were included. A standardized questionnaire was completed for each patient who underwent surgery, and patients with and without SSI were characterized. Patients and ward risk factors for SSI were analysed using a multilevel logistic regression model with SSI as binary outcome (two levels: patient and ward). Results Out of 8569 patients from 39 wards, the SSI rate was 2.2%. Micro-organisms were isolated in 144 patients (74%): 35% coagulase-negative staphylococci (N = 51), 23% Staphylococcus aureus (N = 33), 6% Escherichia coli (N = 8). Higher probability of SSI was associated with the duration of preoperative hospitalization, the duration of follow-up, the duration of surgery >75th percentile and the SSI rate in the surgery ward. The residual heterogeneity between wards (median odds ratio: 1.53) was as relevant as duration of preoperative hospitalization (odds ratio: 1.57). Conclusion Although patient risk factors were more strongly associated with SSI occurrence, this study provided evidence for the existence of a ward-level effect. This should be taken into account when considering possible corrective interventions.